2006
DOI: 10.1159/000095502
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Evaluation of Metallic Coronary Artery Stents with Sub-Millimeter Multi-Slice Computed Tomography Using an ECG-Gated Cardiac Phantom: Relationship between In-Stent Visualization and Stent Type

Abstract: The aim of this experimental study was to investigate visualization of various coronary artery stents with sub-millimeter multi-slice spiral computed tomography (MSCT) using a cardiac physical phantom. Four 3-mm stents of various designs were implanted in tubes with an inner diameter of 3 mm to simulate coronary artery. Stents were placed on a cardiac phantom and scanned at different heart rates. Retrospective ECG-gated adaptive segmental reconstruction technique was employed. Profile curves across longitudina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Imaging coronary stents using CT is a technically more demanding task than imaging native coronary arteries. The degree of metal artifacts of stents, including partial volume effects is related to stent material, the size of the diameter, the thickness and strut design [6,[31][32][33][34]. The metal artifact of tantalum is so severe in comparison with other materials that it is considered to be impossible to assess the lumens of the stents made of tantalum by MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging coronary stents using CT is a technically more demanding task than imaging native coronary arteries. The degree of metal artifacts of stents, including partial volume effects is related to stent material, the size of the diameter, the thickness and strut design [6,[31][32][33][34]. The metal artifact of tantalum is so severe in comparison with other materials that it is considered to be impossible to assess the lumens of the stents made of tantalum by MSCT.…”
Section: Discussionmentioning
confidence: 99%
“…High spatial resolution (slice thickness 0.50-0.75 mm) and the dedicated sharp convolution kernel can optimize in-stent visualization. 22,23 Second, cardiac and respiratory motions may adversely affect the diagnostic accuracy of coronary CTA. It has been reported that coronary CTA tends to overestimate the degree of stenosis.…”
Section: Pitfalls and Shortcomings Of Coronary Cta And Mpsmentioning
confidence: 99%